2021
DOI: 10.2139/ssrn.3786643
|View full text |Cite
|
Sign up to set email alerts
|

The Hidden Cost of Bananas: Pesticide Effects on Newborns’ Health

Abstract: We study the effects of aerial fumigation of banana plantations on newborns' birth weight during the period 2015-2017 in Ecuador. We use mothers' addresses and information on the perimeter of the plantations to create an individual measure of newborns' exposure to pesticides. We use this measure to implement three independent identification strategies to address the endogeneity of exposure to aerial fumigations. First, we consider a difference-indifferences strategy that exploits seasonal variations in the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…In addition, export‐bound banana production dominates the agricultural sector in several regions of the Coast, and accumulation of pesticide residues from these plantations has been documented (Deknock et al., 2019). This raises concerns, as previous studies conducted in Ecuador have shown that environmental exposures to pesticides from banana plantations have a negative effect on birth weight (Calzada et al., 2021) and are linked to indicators of genotoxicity in farmers (Hutter et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, export‐bound banana production dominates the agricultural sector in several regions of the Coast, and accumulation of pesticide residues from these plantations has been documented (Deknock et al., 2019). This raises concerns, as previous studies conducted in Ecuador have shown that environmental exposures to pesticides from banana plantations have a negative effect on birth weight (Calzada et al., 2021) and are linked to indicators of genotoxicity in farmers (Hutter et al., 2020).…”
Section: Discussionmentioning
confidence: 99%